Influence of bamboo biochar on mitigating greenhouse gas emissions and nitrogen loss during poultry manure composting - Awasthi, Mukesh Kumar; Duan, Yumin; Awasthi, Sanjeev Kumar; Liu, Tao; Zhang, Zengqiang (Bioresource technology, 2020)
[Display omitted] •Effectiveness of bamboo biochar on nutrient conservation was studied in composting.•Bamboo biochar (BB) notably elevated enzymes activities during co-composting.•Biochar amendment has positive and significant influence of C and N preservation.•Gaseous and environmental factors had intensively correlation with intersection of 68.81%.•10% BB addition has lowest C and N losses with 148.89% and 12.59%. The effectiveness of specific concentrations of bamboo biochar (BB) on nutrient conservation based on gaseous emissions during poultry manure composting was investigated. The results indicate that the total carbon and nitrogen losses were significantly reduced with elevated of biochar from 542.8 to 148.9% and 53.5 to 12.6% (correspondingly with an additive of 0%, 2%, 4%, 6% and 8% to 10% BB dry weight based). The primary contributor was CO2 and NH3 losses (542.3–148.8% and 47.8–10.81%). The enzyme activities related to carbon and nitrogen metabolism indicated a positive and significantly enhanced with high concentration biochar amended composting. Simultaneously, the alteration of total organic carbon and total Kjeldahl nitrogen as well as maturity indexes during ultimate compost also confirmed a high quality product under higher content biochar amended composting. Carbon and nitrogen were best preserved with 10%BB and produced a superior final product. The analysis of a network and heat map illustrated the correlation of gaseous and physicochemical elements as well as enzyme activities, with an intersection of 68.81%.